Development of an inexpensive 3D clinostat and comparison with other microgravity simulators using Mycobacterium marinum - Clary, Joseph L.; France, Creighton S.; Lind, Kara; Shi, Runhua; Alexander, J.Steven; Richards, Jeffrey T.; Scott, Rona S.; Wang, Jian; Lu, Xiao-Hong; Harrison, Lynn (Frontiers in Space Technologies, 2022)
2D and 3D Clinostats are used to simulate microgravity on Earth. These machines continuously alter the sample’s orientation, so the acceleration vector changes faster than the biological endpoint being monitored. Two commercially available microgravity simulators are the Rotary Cell Culture System (Synthecon Inc.), which is a 2D clinostat, and the RPM 2.0 (Yuri), which is a 3D clinostat that can operate as a random positioning machine or in constant frame velocity mode. We have developed an inexpensive 3D clinostat that can be 3D printed and assembled easily. To determine the optimal combination of inner (I) and outer (O) frame velocities to simulate microgravity, two factors were considered: the time-averaged magnitude and the distribution of the acceleration vector. A computer model was developed to predict the acceleration vector for combinations of frame velocities between 0.125 revolutions per minute (rpm) and 4 rpm, and a combination of I=1.5 rpm and O=3.875 rpm was predicted to produce the best microgravity simulation. Two other frame velocity combinations were also used in further tests: I=0.75 rpm and O=3.625 rpm, and I=2 rpm and O=1.125 rpm. By operating the RPM 2.0 in constant velocity mode at these three velocity combinations, the RPM 2.0 algorithm data confirmed that these operating conditions simulated microgravity. Mycobacterium marinum was selected for biological comparison experiments as this bacterium can grow as a biofilm or a planktonic culture. Biofilm experiments revealed that the RPM 2.0 and the 3D clinostat with I=1.5 rpm and O=3.825 rpm produced similar structures in attached biofilm, and similar changes in transcriptome for the bacteria in suspension compared to the normal gravity transcriptome. Operating the 3D clinostat at I=2rpm and O=1.125 rpm, and the Synthecon 2D clinostat in simulated microgravity orientation at 25 rpm resulted in the same decreased planktonic growth and increased rifampicin survival compared to normal gravity. This study validates the inexpensive 3D clinostat and demonstrates the importance of testing the operating conditions of lab-developed clinostats with biological experiments.